A typology for intraseasonal oscillations. (3rd April 2013) - Pohl, Benjamin; Camberlin, Pierre
ABSTRACT This descriptive study attempts to document the diversity of intraseasonal oscillations (ISO) propagative and spatial patterns, as inferred from outgoing longwave radiation (OLR) variability. Main ISO events over the Indo‐Pacific Warm Pool are first extracted using a local mode analysis (LMA) applied on the 20–120‐d filtered OLR on the 1979–2008 period. One hundred and sixty‐nine individual ISO are detected. Their propagative patterns are then objectively regrouped into a few types using a hierarchical agglomerative classification. Three alternative partitionings are retained, depending on the level of details expected from the typology. ISO events first regroup naturally into two well‐separated classes, identifying boreal summer northward‐propagating events and boreal winter eastward‐propagating ones. Retaining a larger number of classes shows that the diversity of the ISO patterns is primarily modulated by the seasonal cycle, with the most pronounced convective perturbations roughly located at the latitude of the Inter‐tropical Convergence Zone in the tropics. When a sufficient number of types are considered, one can obtain several types of ISO events for a given season. Apart from seasonality, the variability in the ISO appears to be related to surface conditions, such as sea surface temperature. Analysis of the differences between the types suggests that the 'canonical' ISO, often considered in the literature, is actually rather rare and moderately representative of the propagative events taken individually.